A Study of the Interplay between Intuition and Rationality in Valuation Decision Making. Issue 4 (2nd October 2019) - Amidu, Abdul-Rasheed; Boyd, David; Gobet, Fernand
ABSTRACT: There is widespread acceptance that both intuition and rationality can play significant roles in valuation decision-making. However, a study that specifically examines how intuitive and rational approaches interact is still missing. This study addresses this gap by applying cognitive theories of information processing and using a very detailed analysis of verbal protocols to propose a model of cognitive structure that identifies and describes the reasoning of property valuers during a commercial valuation task. The empirical data suggest that valuers start with an established goal and then engage in analytical and intuitive thinking until a valuation outcome has been reached. It is argued that a major reason for effective valuation decision-making, in a real-world context, is that the cognitive processes required by experts' analytical and intuitive thinking demonstrate greater degree of cohesiveness and interrelatedness. The ability of valuers to integrate more intuition into their largely rational decision-making process suggests the need for valuation professional organisations to formally acknowledge intuition as an important component of valuation professional competence and skill requirement and to customise professional valuers' training and development programmes to facilitate the development of appropriate intuitive approaches for effective valuation decision-making.